POTENSI ASAP CAIR KAYU SENGON TERHADAP PENURUNAN KADAR LOGAM TIMBAL (Pb) PADA PENELITIAN MODEL MENGGUNAKAN BIJI KEDELAI (Glycine max) - , NUR ROHMAH L.A; , Prof. Dr. Ir. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Soybeans (Glycine max) is one crop that can accumulate heavy metals. Therefore, soybeans need to be given a pre-treatment so that no accumulation of heavy metals in the human body. The aim of this study was to evaluate the effectiveness of Paraserianthes falcataria (L.) Nielsen wood liquid smoke to reduce Pb content on soybeans and evaluate the role of acid, phenols and carbonyls compounds in Paraserianthes falcataria (L.) Nielsen wood liquid smoke to reduce Pb content on soybeans. This study was divided into four phases, namely the production of liquid smoke from Paraserianthes falcataria (L.) Nielsen wood, modeling Pb contaminant on soybeans, soaking Pb contaminated soybeans using Paraserianthes falcataria (L.) Nielsen wood liquid smoke in various concentrations, i.e 12,5